A heteronormatividade e a graduação em administração - Higashi, Roberto (2016)
The choice of gender issues emerges from latent agenda, which omits or marginalize aspects of organizational life (REED, 2007). Inside the gender issues there is a normative force, heteronormativity, a concept originating in Queer theory, a critique of fe